2003
DOI: 10.1097/01.ede.0000082046.22919.72
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Myocardial Infarction in Rome

Abstract: The results suggest that air pollution increases the risk of myocardial infarction, especially during the warm season. There was a tendency for a stronger effect among the elderly and people with heart conduction disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(116 citation statements)
references
References 41 publications
7
102
2
5
Order By: Relevance
“…Two additional single-city case-crossover studies of air pollution and MI had inconsistent results. A study from Rome, Italy, reported increased risk of MI associated with PM pollution, especially during warm periods, 261 but a study from King County, WA, observed no PM-MI associations. 262 In a much larger case-crossover study using data from 21 U.S. cities with Ͼ300,000 MI events, a 20-g/m 3 increase in PM 10 ambient concentration was associated with a 1.3% (95% CI, 0.6%-2%) increased risk of MI.…”
Section: Short-term Exposure and Cardiovascularmentioning
confidence: 98%
“…Two additional single-city case-crossover studies of air pollution and MI had inconsistent results. A study from Rome, Italy, reported increased risk of MI associated with PM pollution, especially during warm periods, 261 but a study from King County, WA, observed no PM-MI associations. 262 In a much larger case-crossover study using data from 21 U.S. cities with Ͼ300,000 MI events, a 20-g/m 3 increase in PM 10 ambient concentration was associated with a 1.3% (95% CI, 0.6%-2%) increased risk of MI.…”
Section: Short-term Exposure and Cardiovascularmentioning
confidence: 98%
“…Several air pollutants, including particulate matter (PM), carbon monoxide (CO), nitrogen oxides (NO x ), sulfur dioxide (SO 2 ) and ozone (O 3 ) have been associated with increased hospitalization and mortality as a result of cardiovascular disease and stroke [1][2][3][4][5][6][7][8][9]. The underlying mechanisms linking air pollutants and increased cardiovascular risk remain unclear, although prior studies have associated exposure to air pollution with activation of inflammatory pathways, production of reactive oxygen species, endothelial injury and dysfunction, arterial vasoconstriction and alterations in blood coagulation factors [2,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that increased PM concentrations mainly affect the cardiovascular and respiratory systems (Peters et al, 1997a(Peters et al, , 1999Gold et al, 2000;Ibald-Mulli et al, 2001;Brook et al, 2002;Devlin et al, 2003;Schulz et al, 2005) and are especially associated with increased cardiovascular hospital admissions (Schwartz, 1999;Zanobetti et al, 2000;Le Tertre et al, 2002;D'Ippoliti et al, 2003;von Klot et al, 2005;Dominici et al, 2006) or increased cardiovascular mortality (Clancy et al, 2002;Forastiere et al, 2005;Zeka et al, 2005;Ostro et al, 2006). The physical or chemical particle properties (e.g.…”
Section: Introductionmentioning
confidence: 99%